Adaptasi Lintas Budaya dan Uji Psikometrik Skala Scholarly Creativity pada Mahasiswa Indonesia - Akbar, Rizqina Ma'rifatu; Akhrani, Lusy Asa; Zaduqisti, Esti; Aziz, Rahmat (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
Scholarly creativity plays a crucial role in scientific innovation and intellectual productivity. However, valid domain-based instruments for assessing this construct remain limited, particularly across diverse linguistic and cultural contexts. This study aimed to adapt the Scholarly creativity subscale of the Kaufman Domains of Creativity Scale (K-DOCS) into Indonesian language and examine its psychometric properties. The transadaptation procedure followed six stages. A total of 504 university students participated in the study, consisting of 353 females and 151 males from 24 universities and 96 academic programs across 15 cities in Indonesia. Exploratory factor analysis revealed a two-factor structure accounting for 56.3%of the total variance, with item loadings ranging from 0.304 to 0.985. The Kaiser–Meyer–Olkin value was 0.868, and Bartlett’s test of sphericity was significant (p < .001), indicating the suitability of the data for factor analysis. The scale demonstrated high internal consistency, with a Cronbach’s alpha coefficient of 0.855. Overall, the findings provide preliminary evidence supporting the reliability and construct validity of the Indonesian version of the Scholarly Creativity Scale for use among university students. This study contributes to culturally sensitive creativity assessment and offers a foundation for further validation and cross-cultural research on domain-based creativity in higher education contexts.